Growth Hormone Deficiency in a Patient with Becker Muscular Dystrophy: A Pediatric Case Report - Valeria Calcaterra; Annachiara Malvezzi; Rossana Toglia; Angela Berardinelli; Elena Bozzola; Mauro Bozzola; Daniela Larizza (Case Reports in Endocrinology)
Objective. To describe a biochemical growth hormone (GH) deficiency and to evaluate therapeutic result in a six-year-old male with Becker muscular dystrophy (BMD). Methods. GH peak was evaluated after response to arginine and insulin. Bone age was evaluated according to Greulich and Pyle method. Results. The GH-supplementary therapy was very effective in terms of growth gain. Conclusion. The possibility of a growth hormone deficiency and treatment with GH in patients with BMD cannot be excluded, especially considering the good therapeutic response.